1996
DOI: 10.1088/0954-3899/22/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic optical model calculations of - nucleus absorption cross sections

Abstract: Calculations of absorption cross sections using a microscopic first-order optical potential for heavy-ion scattering are compared with experiments. In-medium nucleon-nucleon (NN) cross sections were used to calculate the two-body scattering amplitude. A medium-modified first-order optical potential was obtained for heavy-ion scattering using the in-medium two-body scattering amplitude. A partial wave expansion of the Lippmann-Schwinger equation in momentum space was used to calculate the absorption cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It is found that the magnitude of the cross section decreases with density and the differential cross section becomes more isotropic in medium. Experiments on proton-nucleus scattering [228][229][230] seem to be consistent with these predictions. The N N → N ∆ cross section in medium has been studied in Refs.…”
Section: B the Relativistic Transport Modelmentioning
confidence: 63%
“…It is found that the magnitude of the cross section decreases with density and the differential cross section becomes more isotropic in medium. Experiments on proton-nucleus scattering [228][229][230] seem to be consistent with these predictions. The N N → N ∆ cross section in medium has been studied in Refs.…”
Section: B the Relativistic Transport Modelmentioning
confidence: 63%
“…Even though more accurate quark [20], optical [21,22], and relativistic [23] models have been developed, the Tripathi model was chosen because it is used as default in FLUKA (with specific optimisations [16]), TRiP, and SpaceTRiP, it is part of the HK routine used in PHITS, and it is also implemented in Geant4. Additionally, it has many system-dependent free parameters that can be adjusted individually.…”
Section: Introductionmentioning
confidence: 99%